Buyer's Conjoint Preferences For Attributes Of Condominium Properties In Penang - Chan , Yuan Eng (2010)
It is important that developers should understand their buyers’ preferences in relation to the condominium attributes that they are offering to their buyers. The problem is that there are not many research studies conducted to understand the buyer’s preferences for condominium attributes in the context of the medium price-range condominium property market in Penang. This study is the writer’s endeavor to address this problem and to contribute to the existing academic literature.